2018
DOI: 10.1155/2018/8135274
|View full text |Cite
|
Sign up to set email alerts
|

Improved Chicken Swarm Optimization Method for Reentry Trajectory Optimization

Abstract: Reentry trajectory optimization has been researched as a popular topic because of its wide applications in both military and civilian use. It is a challenging problem owing to its strong nonlinearity in motion equations and constraints. Besides, it is a high-dimensional optimization problem. In this paper, an improved chicken swarm optimization (ICSO) method is proposed considering that the chicken swarm optimization (CSO) method is easy to fall into local optimum when solving high-dimensional optimization pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…In the cloud computing domain, CSO has been used to solve deadlock-free migration of the virtual machine (VM) [28] and dynamic task scheduling problem [29]. In the military field, CSO is applied to optimize the warhead's reentry trajectory [30] and ascent trajectory of hypersonic vehicles [31]. In the data mining domain, it is used to optimize the K-means clustering algorithm [32], adaptive neurofuzzy inference system [33], and feature selection problem [34].…”
Section: Optimization On Engineering Problemsmentioning
confidence: 99%
“…In the cloud computing domain, CSO has been used to solve deadlock-free migration of the virtual machine (VM) [28] and dynamic task scheduling problem [29]. In the military field, CSO is applied to optimize the warhead's reentry trajectory [30] and ascent trajectory of hypersonic vehicles [31]. In the data mining domain, it is used to optimize the K-means clustering algorithm [32], adaptive neurofuzzy inference system [33], and feature selection problem [34].…”
Section: Optimization On Engineering Problemsmentioning
confidence: 99%
“…(c) To preserve an adequate diversity during the searching process: an exploration dynamic operator and a kind of elitist crossover operator inspired by the ideas discussed by Wu et al [29] have been implemented in this work. The authors developed an Improved Chicken Swarm Optimization Method applied to calculate reentry trajectories.…”
Section: Social Intelligent Paradigm Optimization Andmentioning
confidence: 99%
“…In the field of control, the CSO algorithm has also proven to be a good algorithm. For example, in [26], Li et al showed a chicken swarm-based method for ascent trajectory optimization of hypersonic vehicles; in [27], Amador-Angulo et al presented an optimal design of fuzzy logic systems through a Chicken Search Optimization Algorithm applied to a benchmark problem; in [28], Liang et al presented an improved Chicken Swarm Optimization Algorithm and its application in robot path planning; in [29], Mu et al presented an optimal trajectory planning for robotic manipulators using chicken swarm optimization; and in [30], Wu et al presented an improved Chicken Swarm Optimization method for reentry trajectory optimization.…”
Section: Introductionmentioning
confidence: 99%